H Hubungan Dukungan Sosial Keluarga Dengan Efikasi Diri Remaja Di SMAN 1 Banjarmasin - Mariatul; Dhian Ririn Lestari; Eka Santi (Journal of Nursing Invention, 2024)
Background: Adolescence is a transitional period from childhood to adulthood. During adolescence, changes occur involving three aspects: biological, cognitive, and socio-emotional. Adolescence is referred to as a period of "storm and stress." Adolescents are not free from problems that can arise from various factors (both internal and external). Adolescents need support, with the most important support coming from family social support, to build self-efficacy and avoid stress. Objective: This study aims to determine the relationship between family social support and self-efficacy in adolescents at SMA Negeri 1 Banjarmasin. Method: This research is a quantitative study with a cross-sectional approach, using a stratified random sampling technique (n=258). The research instruments used include a demographic data questionnaire, the Perceived Social Support-Family (PSS-Fa) scale, and the General Self-Efficacy Scale. Data analysis was conducted using the Spearman test. Result: The results show a relationship between family social support and self-efficacy in adolescents (p=0.760 <0.05). The data indicate that the majority of adolescents have poor family social support and low self-efficacy. Conclusion: he majority of adolescents at SMA Negeri 1 Banjarmasin have poor family social support and low self-efficacy. Thus, it is concluded that there is a strong relationship between family social support and self-efficacy in adolescents at SMA Negeri 1 Banjarmasin